2007
DOI: 10.1016/j.ydbio.2007.02.034
|View full text |Cite|
|
Sign up to set email alerts
|

The serine/threonine kinase dPak is required for polarized assembly of F-actin bundles and apical–basal polarity in the Drosophila follicular epithelium

Abstract: During epithelial development cells become polarized along their apical-basal axis and some epithelia also exhibit polarity in the plane of the tissue. Mutations in the gene encoding a Drosophila Pak family serine/threonine kinase, dPak, disrupt the follicular epithelium that covers developing egg chambers during oogenesis. The follicular epithelium normally exhibits planar polarized organization of basal F-actin bundles such that they lie perpendicular to the anterior-posterior axis of the egg chamber, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
71
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 54 publications
7
71
0
5
Order By: Relevance
“…As Pak becomes localized basally when the basal F-actin begins to polarize, it could be negatively regulating Rho1 activation only at this end of the follicle cells. To see whether this was the case we looked for an increase in GTPRho1 at the basal end of follicle cells in pak mutant egg chambers but saw no obvious difference compared to wild type (Conder et al 2007) (Figure 4, B-E, and data not shown).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…As Pak becomes localized basally when the basal F-actin begins to polarize, it could be negatively regulating Rho1 activation only at this end of the follicle cells. To see whether this was the case we looked for an increase in GTPRho1 at the basal end of follicle cells in pak mutant egg chambers but saw no obvious difference compared to wild type (Conder et al 2007) (Figure 4, B-E, and data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…pak mutant egg chambers are spherical as they fail to elongate along the A-P axis and they do not develop past stage 10 and therefore never produce mature eggs ( Figure 1C). The inability of pak mutant egg chambers to elongate is likely due to disruptions of the basal F-actin, which is less dense, disorganized, and no longer polarized perpendicularly to the A-P axis (Conder et al 2007). The F-actin architecture in pak mutant egg chambers does not have a distinct orientation as seen in wild-type egg chambers and is highly disrupted.…”
mentioning
confidence: 92%
See 3 more Smart Citations